Synthesis and properties of cyclic phosphadiynes - Popp, Ralf; Gleiter, Rolf; Rominger, Frank (Tetrahedron letters, 2000)
The first synthesis of medium-sized cyclic 1-arylphosphadiynes is reported. Details of the molecular structure of 1-phenylphosphacyclododeca-3,10-diyne sulfide (9b) and 1-(2′,4′,6′-tri-tert-butylphenyl)phosphacyclodeca-3,8-diyne sulfide (9c) are reported.